The Influence of the Cooperative Economics Learning Process on the Cooperative Interest of Economics Education Students: A Case Study of Economics Education Study Program Students at Makassar State University - Mustari, Mustari; Arisah, Nur (International journal of technology and education research, 2025)
This study aims to examine the influence of the cooperative economics learning process on the cooperative interest of students in the Economics Education Study Program at Makassar State University. Cooperative economics learning is considered important to improve students' understanding of cooperatives as an economic model based on collectivity and sustainability. However, despite the many benefits of cooperatives, many students are less interested or even unaware of their importance. This study used a descriptive qualitative approach with in-depth interviews, observation, and documentation to explore students' perceptions of cooperatives and the influence of cooperative learning on their interest. The results showed that a learning process that integrates theory and practice can increase students' interest in joining and participating in cooperatives. Students who are directly involved in cooperative activities show a better understanding of cooperative principles and their benefits. However, many students still desire more practical experience and direct involvement in cooperative management. Therefore, it is recommended to increase practical activities and implement more engaging learning methods to increase students' interest and readiness to become involved in cooperatives.